PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PASIEN DI PUSKESMAS WIROBRAJAN KOTA YOGYAKARTA - Sudaryanto, Sudaryanto; Arafah, Riqif (PRIMA EKONOMIKA, 2023)
This study aims to determine the effect of service quality and pharmaceutical facilities on outpatient satisfaction at the Wirobrajan Community Health Center, Yogyakarta City using IBM SPSS for Windows version 22.This research method is quantitative research. The sample from this research was the Wirobrajan Community Health Center, Yogyakarta City with 100 respondents. The analysis technique used is multiple linear regression. This analysis uses the independent variables quality of service and pharmaceutical facilities, while the dependent variable uses patient satisfaction.The results of the t test show that service quality partially has a significant effect on patient satisfaction at Wirobrajan Health Center, Yogyakarta City with a significance value of 0.000. Pharmaceutical facilities partially do not have a significant effect on patient satisfaction at the Wirobrajan Health Center, Yogyakarta City with a significance value of 0.052 and the F test results show that the quality of service and pharmaceutical facilities simultaneously have a positive effect on patient satisfaction at the Wirobrajan Health Center, Yogyakarta City. The multiple linear equation shows Y= 0.102+0.212.X1+0.136X2. The R value = 0.839 shows that the variables of service quality and pharmaceutical facilities have a very strong relationship with patient satisfaction. R2= 0.704 shows that the variable quality of pharmaceutical services and facilities contributes to patient satisfaction by 70.4% outside this research has the ability to contribute 29.6% Keywords: Service Quality, Pharmaceutical Facilities, Patient Satisfaction